El proceso de gentrificación en el centro histórico de Santa Cruz de Lorica en el marco del desarrollo de la renovación urbana (2004-2019) (2021)
This research analyzes the gentrification process experienced by the Historic Center-CH of Santa Cruz de Lorica in the framework of urban renewal 2004-2019, describing the process based on the POT (2002-2010) and the PEMP (2004); In addition, to demonstrate the role of the agents or causes that have promoted the gentrification process and the population dynamics of CH of Santa Cruz de Lorica, product of urban renewal processes. This research starts from a qualitative approach whose variables are land uses: residential, institutional, commercial, services; conservation levels of architectural heritage; refunctionalization of equipment and infrastructure (abandoned, occupied, restored and in the process of restoration); public space (parks, squares, squares), classification of agents promoting gentrification (state, real estate, tourism and owner), and the population (traditional families, occupation and population origin). Through the collection of primary and secondary information, in which the primary one was through observational field, photographic records and interview, the secondary information was through books, magazines, research papers, documents of the Mayor's Office of Santa Cruz de Lorica: Territorial Planning Plan-POT of the municipality of Santa Cruz de Lorica (2002-2010), Special Patrimony Management Plan-PEMP (2004), Strategic Tourism Development Plan-PEDT (2016-2025). Through the urban renewal process generated by the POT and the PEMP, it has been found that since its execution there have been changes in land use, changed from residential use to commercial and service and institutional use, as well as how refunctioning has been generated of some buildings of the CH such as the Gonzales, Caraballo and the Isla building. In the same way, the process of urban renewal has recovered, reorganized and generated public space which has led to generate greater recovery in the soil, higher cost in public services, which has meant that many properties that were previously residential are used for commerce, services or that were already destined for commerce and services have transformed under the new Global economic dynamics.